2021
DOI: 10.3390/ijms22042112
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of the Zygophyllum xanthoxylum Aquaporin, ZxPIP1;3, Promotes Plant Growth and Stress Tolerance

Abstract: Drought and salinity can result in cell dehydration and water unbalance in plants, which seriously diminish plant growth and development. Cellular water homeostasis maintained by aquaporin is one of the important strategies for plants to cope with these two stresses. In this study, a stress-induced aquaporin, ZxPIP1;3, belonging to the PIP1 subgroup, was identified from the succulent xerophyte Zygophyllum xanthoxylum. The subcellular localization showed that ZxPIP1;3-GFP was located in the plasma membrane. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…In addition, overexpression of PIP genes improves the salt resistance of plants. For example, overexpression of ScPIP1 [35], ZxPIP1;3 [29], CfPIP1-1, CfPIP1-2, and CfPIP1-4 [36], and MdPIP1;3 [37] improve the salt and drought resistance of transgenic Arabidopsis. Similarly, the current study also showed that EuPIP1;2 improved the salt resistance of transgenic tobacco.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, overexpression of PIP genes improves the salt resistance of plants. For example, overexpression of ScPIP1 [35], ZxPIP1;3 [29], CfPIP1-1, CfPIP1-2, and CfPIP1-4 [36], and MdPIP1;3 [37] improve the salt and drought resistance of transgenic Arabidopsis. Similarly, the current study also showed that EuPIP1;2 improved the salt resistance of transgenic tobacco.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that PIP genes reduce the MDA content and membrane damage under stress in transgenic plants, and assist transgenic plants to maintain a relatively healthy physiological state under stress, thereby improving stress resistance. Under drought or salt stress, transgenic plants that overexpress ScPIP [35], ZxPIP1;3 [29], MSPIP2;2 [32], CmPIP1 [17], or ScPIP2-1 [40] have a lower MDA content than WT plants. The present study showed that under drought stress, the MDA content of transgenic plants was significantly lower than that of WT plants, indicating that the membrane damage suffered by EuPIP1;2-overexpressing plants was not as severe as that experienced by WT type.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In wheat, TaTIP4;1 serves as a positive regulator of salt tolerance by modulating water relations and the accumulation of Na + ( Wang et al, 2022 ). ZxPIP1;3 conferred transgenic plants with salt tolerance by regulating water status and reducing ion toxicity ( Li et al, 2021 ). MaPIP1;1 enhanced banana salt tolerance via affecting the contents of Na + and K + ( Xu et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…The authors suggested that MpCML40 contributed to the proline accumulation for reducing the damage caused by reactive oxygen species. A stress-induced aquaporin, ZxPIP1;3 , was identified by Li et al from succulent xerophyte, is belonging to the PIP1 subgroup of plasma membrane intrinsic proteins (PIPs) [ 7 ]. The overexpression of ZxPIP1;3 in Arabidopsis showed certain improvements in growth and physiological attributes which lead to more efficient photosynthesis under salinity and drought stresses.…”
mentioning
confidence: 99%